Comparative oral bioavailability of geniposide following oral administration of geniposide, Gardenia jasminoides Ellis fruits extracts and Gardenia herbal formulation in rats. (11th December 2013) - Cheng, Sharleen; Lin, Lie-Chwen; Lin, Chi-Hung; Tsai, Tung-Hu
Abstract: Objective: The aim of this study was to compare the oral bioavailability and pharmacokinetic data between pure compound of the major active component, single herbal extract and complex herbal formulation by determining bioavailability of geniposide in each group following intravenous and oral administrations. Methods: A conscious and freely moving rat model was used in this experiment to avoid the stress caused by restraint or anaesthesia. The pure compound of geniposide, Gardenia fruits (Chinese name: Zhi-Zi), and extracts of a Gardenia herbal formulation (Chinese name: Zhi-Zi-Chi-Tang) were administered at doses of 200 mg/kg, 4.69 g/kg and 10.82 g/kg for oral administration and fed by gavages to rats, respectively. The earlier doses are equivalent to geniposide administration dose of 200 mg/kg. Key findings: The results show that after oral administration of geniposide, Gardenia fruits and Gardenia herbal formulation, the bioavailability were 4.23%, 32.32% and 27.17%, respectively. The results of oral bioavailability of geniposide also suggest that Gardenia fruits extract, single herb, is a more efficient way for geniposide, pure compound, absorption than traditional herbal formulation administration and direct pure compound administration. Conclusions: The conclusion reveals that herbal ingredient–ingredient or herb–herb interaction may affect the oral absorption of geniposide-related herbal formulation.